Organizational internal and external resources as drivers of success in product development: A conceptual model - Trifandi Lasalewo; Budi Hartono; Subagyo Subagyo; Hari Agung Yuniarto (Jurnal Teknosains, 2022)
Products succeed if they meet customer needs and expectations. However, the capability of a corporation or organization to achieve the success of its products is determined by many variables, including being able to exploit its internal and external resources. This study is aimed to test variables that generate impacts on successful products. With the aid of research tool Vosviewer, a bibliometric network is mapped based on Scopus data of previous publications. Then an in-depth analysis is conducted on variables that are identified with a systematic review technique, in which corporational internal and external factors that have great significance on the success of products are grouped. By virtue of this research, a conceptual model is built to describe how corporational internal and external resources affect product success. It is found driving forces in promoting success of products are four internal resources like product characteristics, organization & management characteristics, innovative, and knowledge sharing, and one external resource market characteristics. The conceptual model built in this study would serve as a model for measuring the success of product development in the subsequent studies.